Implications of Empowerment Status in Agricultural Production Capabilities of Rural Women in Selected States of Nigeria - Oluwaseun Aderonke Adeleke; Luqman Abiodun Akinbile (Journal of Agricultural Extension, 2019)
Rural women across the globe possess great potentials for increasing agricultural productivity and development of any nation but they are often not empowered. Empowerment of rural women has been found to significantly impact livelihood of households, communities and the nation at large. This study assessed the empowerment status of rural women in Nigeria using five main indicators; decision-making, economic, social, political and time-use empowerment. Multi-stage sampling technique was used to randomly select four States from the six agricultural zones in Nigeria; Oyo, Edo, Benue and Sokoto States. From each state, 10% of Local Government Areas (LGAs) were randomly selected making a total of nine LGAs. Two communities were randomly selected from each LGA to give 18 rural communities. Rural women were systematically sampled proportionate to size of each community to give 261 respondents. Data were analysed using descriptive and inferential statistics like PPMC and ANOVA.  The findings of the study revealed that 66.7% of the respondents were between the age range of 21-30 years, 43.7% had no formal education and 39.8% were crop farmers. Respondents that were traders engaged in small scale business and 11.5% had access to personal land for farming activities. Across the States, respondents had low decision-making ( =32.4), high economic ( = 83.1), high social ( = 7.6), low political ( = 11.7) and high time-use ( = 20.7) empowerment and a low empowerment status ( = 155.5) across States. ANOVA result shows that there was a significant difference (F=47.615) in the empowerment status of respondents across selected States with Oyo State having the highest (168.1Â±14.6) and Benue State having the lowest (138.4Â±19.4) empowerment status. The study concluded that respondents in Oyo state were more empowered than respondents in other three states in the five indicators used in this study. It was recommended that rural women should be empowered by organising seminars on self-help projects and giving them voice which will help them to contribute significantly to their family and also enable them have a sustainable farm community.